RESPONSE TO IMMUNOSUPPRESSIVE THERAPY IN PATIENTS OF ACQUIRED APLASTIC ANAEMIA: A SINGLE CENTER EXPERIENCE FROM A DEVELOPING COUNTRY - Maryam Khan; Raheel Iftikhar; Qamar un Nisa Chaudhry; Syed Kamran Mehmood; Tehniat Faraz; Tariq Ghafoor; Nighat Shahbaz; Mehreen Ali Khan; Ghassan Umair Shamshad; Tariq Azam Khattak (Journal of Ayub Medical College Abbottabad, 2022)
Background: Aplastic Anaemia (AA) is characterized by pancytopenia and hypocellular marrow. Immunosuppressive therapy (IST) SHOWS impressive haematological response; however, risk of relapse and clonal evolution persists. The objective of the study is to assess response to IST in patients with aplastic anaemia. Methods: A retrospective single centre study at AFBMTC / NIBMT for patients of acquired AA was conducted from January 2005 to December 2019.Inclusion criteria included diagnosed cases of acquired AA receiving IST for at least 12 weeks and age >2 years. IST included cyclosporine (CsA) alone, CsA + androgens, CsA + rabbit anti thymocyte globulin (rATG), CsA + horse anti thymocyte globulin (hATG). Primary outcome measure was response to IST; secondary outcome measure was overall survival (OS). Results: A total of 513 patients received IST. Median age was 23 years (range 2-97 years). In study cohort, 155 (30.2%) patients responded to the IST, 63 (12.3%) achieved complete response (CR) while 92 (17.9%) achieved partial response (PR). The ORR of CsA in NSAA, SAA and VSAA was 52.6%, 28.10% and 10% respectively; whereas ORR of CsA + rATG in NSAA, SAA and VSAA was 50%, 35.1% and 22.5% respectively. OS was 38% at a median follow up of 36 months. There was a significant difference in the survival distributions of different treatment modalities (p=0.016). Median survival time 60 months (CsA), 9 months (CsA+ androgens) and 39 months (CsA+ rATG/hATG.) Conclusion: In resource constrained settings, single agent CsA remains a reasonable alternative with modest activity and acceptable side effect profile.